ANALISIS KESULITAN SISWA DALAM KEMAMPUAN BERPIKIR KRITIS UNTUK MENYELESAIKAN SOAL SUKU BANYAK - Susanti, Nawal Ika; Asnawi, Muhammad Hasan (MAXIMA : Jurnal Pendidikan Matematika, 2025)
The purpose of this research is to analyze the level of difficulty students face in critical thinking skills to solve polynomial problems.This research uses a quantitative approach by employing data difficulty level analysis and critical thinking level analysis. The research sample consisted of 30 students from the XI IPA 3 class at SMA Darussalam. The results of this study show the level of students' critical thinking skills in solving polynomial problems consisting of 5 questions. In terms of students' critical thinking abilities, they fall into the critical thinking category on question no. 1 with indicators of identifying, problem-solving, evaluating, and analyzing polynomial problems. Looking at the level of mistakes made by the students, the highest was on question no. 2 with a difficulty percentage of 53.3%, which corresponds to 16 students. Meanwhile, the lowest error rate was on question no. 3, which was 20%, or 6 students.